A Search for Missing Links: Specifying the Relationship Between Leader-Member Exchange Differentiation and Service Climate - AYSUNA TÜRKYILMAZ, CEYDA (SAGE PUBLICATIONS INC, 2016)
We search for missing links in how the different social exchange relationships employees have with supervisors (i.e., leader-member exchange [LMX] differentiation) affect their unit service climate perceptions. Drawing on a social comparison perspective, we propose a model in which the different relationships service employees establish with supervisors negatively impact unit service climate through elevated unit relationship conflict. We further suggest that unit relationship conflict plays a mediating role as customer variability increases. Using data from head nurse-nurse relationships in 56 units of two major hospitals, our findings support the proposed linkages as well as reveal that employee perceptions of customer variability strengthen the troublesome positive link between LMX differentiation and unit relationship conflict. The results also indicate that unit relationship conflict mediates the relationship between LMX differentiation and unit service climate when customer variability is high but not low. Our results paint a more nuanced picture of the missing link in the leadership-climate interface by studying the dark side of leadership, a perspective that has yet to receive much scholarly attention. Findings reveal that managers who desire to keep relationship conflict in check need to keep LMX differentiation to a minimum, especially when customer variability is high compared to low.
Keywords: service climate; leader-member exchange differentiation; social comparison perspective; customer variability; relationship conflict; SOCIAL-COMPARISON PROCESSES; INTRAGROUP CONFLICT; PRODUCT DEVELOPMENT; TEAM PERFORMANCE; FIRM PERFORMANCE; RESEARCH AGENDA; SAFETY CLIMATE; WORK GROUPS; CUSTOMER; MEDIATION